Rucaparib: An emerging parp inhibitor for treatment of recurrent ovarian cancer. (May 2018) - Musella, Angela; Bardhi, Erlisa; Marchetti, Claudia; Vertechy, Laura; Santangelo, Giusy; Sassu, Carolina; Tomao, Federica; Rech, Francesco; D'Amelio, Renzo; Monti, Marco; Palaia, Innocenza; Muzii, Ludovico; et al.
Highlights: Ovarian cancer, the deadliest of gynecological cancers, has a 70% recurrence rate. Ovarian cancer presents homologous recombination deficiencies in 50% of cases. PARP inhibitors manifest synthetic lethality in BRCA mutated cancers. Rucaparib, a PARP inhibitor, is effective in patients with "BRCAness" phenotype. A complex HRD assay predicts response to Rucaparib by defining the degree of LOH. Abstract: Recently, Poly-ADP-Ribose Polymerase (PARP) inhibitors are one of the most intensively studied group of antiblastic agents for the management of recurrent ovarian cancer. Among this family, Olaparib was the first to be approved by European Medicines Agency as maintenance therapy post-response to platinum-based chemotherapy for recurrent ovarian cancer in women with deleterious BRCA1/2 mutation. Following that, the Food and Drug Administration (FDA) approved Olaparib monotherapy as fourth or later line of treatment in advanced ovarian cancer with deleterious germ-line BRCA1/2 mutation. On March 2017, Niraparib, was approved as maintenance treatment of patients with recurrent epithelial ovarian, who are in complete or partial response to platinum-based chemotherapy, independently of BRCA mutation. Rucaparib inhibits PARP-1, 2 and 3, PARP-4, -12, -15 and -16, as well as tankyrase 1 and 2. On December 2016, it was granted accelerated approval by the FDA, based on data from two multicenter, single arm, phase II trials that evaluated the efficacy of Rucaparib in patients with deleterious, germline and/or somatic BRCA mutation-associated, advanced OC, who have been treated with two or more lines of chemotherapy. The maximum tolerated dose reported was 600 mg twice a day administered orally. Phase III studies are currently ongoing to further validate the efficacy of Rucaparib in the treatment setting and explore its usefulness in a maintenance setting as well. The focus of our review is to report the most recent investigations and clinical progress regarding Rucaparib for treatment of recurrent ovarian cancer.